Climate change and agricultural productivity in Myanmar: Application of a new computable general equilibrium (CGE) model - Henning Tarp Jensen; Marcus Keogh-Brown; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Myanmar is facing climate change (CC) induced changes to the productivity of their critically important rice sector over the coming century. Moreover, the recent five-year Myanmarese Agriculture Development Strategy (ADS) sets out a vision of achieving an '…inclusive, competitive, food and nutrition secure, climate change resilient, and sustainable agricultural system…' by 2030. In this paper, we investigate the productivity pillar of the ADS strategy. Specifically, we employ a newly developed dynamically recursive 2021-40 computable general equilibrium model for Myanmar to analyse seven current and future CC scenarios for stateand region-specific paddy yield changes during the 2020s, 2050s, and 2080s, derived from IIASA and FAO's Global Agro-Ecological Zones GAEZ V.3 model scenarios, allowing us to analyse the relative importance of both rainfed and irrigation farming practices and of high input-use and low input-use technologies, and how these important agricultural technology farming decisions interact with CC-induced paddy yield changes. Our results suggest that, while Myanmarese smallholders, using low input-use farming technologies, may face small or even negative economic impacts from CC-induced rice paddy yield changes, high input-use farmers, across all states and regions, will benefit from CC-induced paddy yield changes towards the end of the century, highlighting the importance of expanding access to high input-use technologies, e.g. via expanded use of extension services and by providing better access to credit for smallholder farmers. We also find, counterintuitively, that farming households using irrigation farming practices will benefit less from CC-induced paddy yield changes compared to households using rainfed farming practices. Finally, our results point to strong differences in CC impacts between states and regions, indicating that mitigating action should be focussed on exposed regions such as the critically important Ayeyarwady region.
Keywords: C68; Q1; Q51; Q54; 330; Myanmar; agricultural technology; climate change; rice productivity; computable general equilibrium model